Analyzing the Reality of Professional Quality of Life and Its Impact on Job Stability among Kindergarten Teachers in Private Schools - Al-Zahrani, Nada Khamis (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the work-life quality of kindergarten teachers in private schools in southern Makkah and examines how this reality affects their job stability and motivation to remain in the educational field. Using a basic interpretive qualitative approach, semi-structured interviews were conducted with eight purposively selected teachers from six private schools. The interviews addressed dimensions of work-life quality, daily challenges, and their impact on teachers' sense of security and professional stability. Results identified five main challenges: lack of job security (as all teachers, 100%, stated that annual contracts undermine stability and increase anxiety), low salaries, limited participation in decision-making, excessive workloads relative to available resources, and insufficient administrative support and recognition. Teachers indicated that these factors negatively affect job satisfaction and prompt many to consider leaving or seeking more stable employment. The study recommends urgent institutional reforms: regularizing contracts, providing fair material and moral incentives, improving physical and psychological work environments, activating participatory management, and ensuring effective administrative support and regular professional training. These actions would enhance job satisfaction, reduce turnover intentions, and achieve sustainable educational quality in the private kindergarten sector. The study’s significance lies in offering practical recommendations to improve work environments and support education quality in private kindergartens.
Keywords: Work-life quality; job stability; kindergarten teachers; private schools; job satisfaction; work environment